Creating the future of work : imaginaries in an era of digitalization - Anette Hallin; Christoffer Andersson; Lucia Crevani; Caroline Ingvarsson; Chris Ivory; Inti Lammi; Eva Lindell; Anna Uhlin (Creating the future of work : imaginaries in an era of digitalization, 2025)
"This timely book explores the ways in which the future of work and associated digital technologies are imagined in contemporary society. Drawing on a wealth of original research, the book features detailed case studies that link broad sociological concepts to everyday practice. Building on the view that ideas about the future matter, the authors examine four imaginaries, namely work as rational, work as human-machine collaboration, work as freedom and work as self-improvement. They discuss how these imaginaries of work and technology risk shaping unwanted futures, and outline different scenarios that reflect an ideal future working world. Creating the Future of Work is an indispensable resource for academics and students of business and management, organisation studies, employment relations, and the sociology of work and organisations. Researchers, policymakers and business professionals interested in creating a positive working environment and in deploying constructive technology will also find this book to be of great importance"–
10.4337/9781035324484; 10.4337/9781035324484